Epidemiology of injuries in National Collegiate Athletic Association women's volleyball: 2014-2015 through 2018-2019 - Chandran, A.; Morris, S. N.; Lempke, L. B.; Boltz, A. J.; Robison, H. J.; Collins, C. L. (Journal of Athletic Training, 2021)
Context: Women's volleyball is a globally popular sport with widespread participation at the National Collegiate Athletic Association (NCAA) level. Background: Routine examinations of NCAA women's volleyball injuries are important for recognizing emerging injury-related patterns in this population. Methods: Exposure and injury data collected in the NCAA Injury Surveillance Program during the 2014-2015 through 2018-2019 athletic years were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differences in injury rates. Results: The overall injury rate was 6.73 per 1000 athlete-exposures. Knee (14.6%) and ankle (13.8%) injuries accounted for the largest proportion of all reported injuries, and most injuries were attributed to overuse (26.1%) or noncontact (22.7%) mechanisms. Lateral ankle ligament complex tears (11.1%) and concussions (7.3%) were the most commonly reported specific injury. Summary: Results indicate an increasing burden of practice-related injuries and the need to further examine overuse injuries. Lower-extremity injury prevention strategies and mechanisms of concussion also warrant further attention.